Compact adaptive optics line scanning ophthalmoscope - Mujat, Mircea (2009)
We have developed a compact retinal imager that integrates adaptive optics (AO) into a line scanning ophthalmoscope (LSO). The bench-top AO-LSO instrument significantly reduces the size, complexity, and cost of research AO scanning laser ophthalmoscopes (AOSLOs), for the purpose of moving adaptive optics imaging more rapidly into routine clinical use. The AO-LSO produces high resolution retinal images with only one moving part and a significantly reduced instrument footprint and number of optical components. The AO-LSO has a moderate field of view (5.5 deg), which allows montages of the macula or other targets to be obtained more quickly and efficiently. In a preliminary human subjects investigation, photoreceptors could be resolved and counted within ~0.5 mm of the fovea. Photoreceptor counts matched closely to previously reported histology. The capillaries surrounding the foveal avascular zone could be resolved, as well as cells flowing within them. Individual nerve fiber bundles could be resolved, especially near the optic nerve head, as well as other structures such as the lamina cribrosa. In addition to instrument design, fabrication, and testing, software algorithms were developed for automated image registration and cone counting.